The Microbiota Is Essential for the Generation of Black Tea Theaflavins-Derived Metabolites - Chen, Huadong; Hayek, Saeed; Rivera Guzman, Javier; Gillitt, Nicholas D.; Ibrahim, Salam A.; Jobin, Christian; Sang, Shengmin (PloS one, 2012)
Theaflavins including theaflavin (TF), theaflavin-3-gallate (TF3G), theaflavin-3'-gallate (TF3'G), and theaflavin-3,3'-digallate (TFDG), are the most important bioactive polyphenols in black tea. Because of their poor systemic bioavailability, it is still unclear how these compounds can exert their biological functions. The objective of this study is to identify the microbial metabolites of theaflavins in mice and in humans. In the present study, we gavaged specific pathogen free (SPF) mice and germ free (GF) mice with 200 mg/kg TFDG and identified TF, TF3G, TF3'G, and gallic acid as the major fecal metabolites of TFDG in SPF mice. These metabolites were absent in TFDG- gavaged GF mice. The microbial bioconversion of TFDG, TF3G, and TF3'G was also investigated in vitro using fecal slurries collected from three healthy human subjects. Our results indicate that TFDG is metabolized to TF, TF3G, TF3'G, gallic acid, and pyrogallol by human microbiota. Moreover, both TF3G and TF3'G are metabolized to TF, gallic acid, and pyrogallol by human microbiota. Importantly, we observed interindividual differences on the metabolism rate of gallic acid to pyrogallol among the three human subjects. In addition, we demonstrated that Lactobacillus plantarum 299v and Bacillus subtilis have the capacity to metabolize TFDG. The microbiota is important for the metabolism of theaflavins in both mice and humans. The in vivo functional impact of microbiota-generated theaflavins-derived metabolites is worthwhile of further study.